2014
DOI: 10.5209/rev_cmpl.2014.v25.n1.45353
|View full text |Cite
|
Sign up to set email alerts
|

Los útiles óseos “poco elaborados” en el Paleolítico inferior y medio y su continuidad en el Paleolítico superior. Una revisión historiográfica

Abstract: Los útiles óseos "poco elaborados" en el

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…With the exception of the complete teeth, metatarsal and proximal phalanx from Gough’s Cave, we are not aware of any other records of complete bones used as knapping tools from a Magdalenian context. The diversity of materials used as knapping percussors during the Magdalenian is illustrated at sites such as Gönnersdorf [ 110 , 111 , 113 , 114 ] and Oelknitz [ 112 ] in Germany, and La Vache, in France [ 100 , 101 ], where bone or ivory as well as pebbles were used for knapping. Evidence from the French sites of Enlène [ 95 ] and Laugerie-Haute [ 1 ] indicates that antlers were also modified to make knapping hammers during the Magdalenian.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…With the exception of the complete teeth, metatarsal and proximal phalanx from Gough’s Cave, we are not aware of any other records of complete bones used as knapping tools from a Magdalenian context. The diversity of materials used as knapping percussors during the Magdalenian is illustrated at sites such as Gönnersdorf [ 110 , 111 , 113 , 114 ] and Oelknitz [ 112 ] in Germany, and La Vache, in France [ 100 , 101 ], where bone or ivory as well as pebbles were used for knapping. Evidence from the French sites of Enlène [ 95 ] and Laugerie-Haute [ 1 ] indicates that antlers were also modified to make knapping hammers during the Magdalenian.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Interestingly, bone tools are quite abundant in this upper part of the Mousterian sequence. Among the bone tools, retouchers represent the predominant type, but other tools, such as chisels or polishers, have been also identified (Table S2 ) 26 , 72 . The faunal assemblage in these levels is dominated by red deer ( Cervus elaphus ), large bovids ( Bos/Bison ), Iberian wild goats ( Capra pyrenaica ) and, to a lesser extent, horses ( Equus ferus ) (Tables S3 and S4 ) 36 , 73 .…”
Section: Contextmentioning
confidence: 99%
“…In recent years we have also observed the increasing number of evidence for the practice of non-utilitarian activities, such as the burial of dead 11 , 12 , artistic behavior 13 , 14 , the elaboration and display of ornaments 15 20 , the use of pigments 21 , 22 or the building up of structures such as the ring from Bruniquel 23 . From a purely technological point of view, Neandertals mastered the use of fire 24 , developed complex technological procedures, such as creating birch glue 25 and started using bone tools more systematically 26 , 27 . In regard to lithic technology, several features interpreted as markers of modern behavior, such as the use of hafted tools 28 , the long distance transport of raw materials 29 , the production and use of small tools 30 , or the development of blade technologies 31 are more common in Neandertal technology than previously thought 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, taphonomic analyses revealed that there are natural agents that can produce “pseudo‐artefacts” (Brain, 1980; D'Errico & Giacobini, 1988; Villa & D'Errico, 2001). However, today, we know that undoubtedly bones were sometimes employed as tools after minimal or null prior modification: the digging sticks from Swartkrans are a good example (D'Errico & Backwell, 2003), and other cases have been published for the Lower and Middle Palaeolithic, both in Europe and in Africa (Barham et al, 2000, 2002; D'Errico, 2007; Mozota, 2014).…”
Section: Introductionmentioning
confidence: 99%